The Role of Geography Teachers in Pekanbaru High Schools in Adapting Methods to Student Characteristics and Local Context - Ocha Fathica Rizty; Siti Hotijah; Tiara Ayu Safitri Dewi; Ade Irma (Council: Education Journal of Social Studies, 2026)
The diversity of students’ characteristics and the uniqueness of the local context of Pekanbaru City require high school Geography teachers to adapt their teaching methods in order to create meaningful learning experiences. This study aims to analyze the role of Geography teachers in adapting instructional methods to students’ characteristics and the local context in senior high schools in Pekanbaru. The research employed a qualitative approach with a descriptive method. Data were collected through in-depth interviews, classroom observations, and document analysis involving Geography teachers in several senior high schools. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results indicate that Geography teachers play an active role in adjusting teaching methods to students’ characteristics by applying various strategies, such as contextual discussions, local case studies, the use of the surrounding environment as a learning resource, and the utilization of relevant instructional media. Furthermore, the local context of Pekanbaru, including its geographical, environmental, and socio-cultural conditions, is integrated into the learning process to enhance students’ understanding and engagement. These methodological adaptations are shown to improve students’ participation, conceptual understanding, and the relevance of Geography learning